O.12.1Transforming Medical Students: Reviewing Communication Skills Training Using OSCEs: Presenter(s): Mehmet Gokhan Gonenli, Koc University School of Medicine, Turkey. (April 2023) - Chizzo, Jacob; Dandekar, Sucheta
Abstract : Background: A structured clinical communication skills training program was introduced in 2019 at the Koc University School of Medicine. Handling sensitive issues (HSI) and breaking bad news (BBN) were introduced as two specific communication skills in the program. This study aimed to measure the effectiveness of the HSI and BBN training on students' communication skills Method: Forty-five medical students in their first clinical year were initiated into the program and randomly divided into two groups. The first group received HSI training while the second group received BBN training; one month later, they were interchanged. The training included lectures, video discussions, and role-playings. Students were trained to use NURSE statements for showing empathy, the CDC's 5Ps approach for taking a sexual history, and the six-step SPIKES protocol for BBN. Two different OSCE stations were used to assess students after each training session. Each group encountered a scenario based on the related training; the other station presented a scenario for which they were not trained. Students were graded using a pre-validated checklist. Students also submitted written self-assessments and feedback after the two trainings were completed. The OSCE scores of both groups were analyzed and compared. Findings: A total of 43 students completed the training. In both the HIS and BBN groups, the post-training OSCE mean score increased significantly. There was no significant decrease in the mean score of the OSCEs performed one month after the training. Students endorsed the training, saying it would help them face real situations in clinical settings. Discussion: HSI and BBN training significantly improved the students' communication skills. This study's results provide evidence to stakeholders about the importance and effectiveness of the program and encourages us to redesign other communication skills lessons within the curriculum to provide the students with the most efficient and effectual training and practice.